Stable surface expression of invariant chain prevents peptide presentation by HLA-DR. - Roche, P A (1992)
Class II major histocompatibility complex (MHC) molecules are cell surface glycoproteins that bind and present immunogenic peptides to T cells. Intracellularly, class II molecules associate with a polypeptide referred to as the invariant (Ii) chain. Ii is proteolytically degraded and dissociates from the class II complex prior to cell surface expression of the mature class II alpha beta heterodimer. Using human fibroblasts transfected with HLA-DR1 and Ii cDNAs, we now demonstrate that truncation of the cytoplasmic domain of Ii results in the failure of Ii to dissociate from the alpha beta Ii complex and leads to stable expression of class II alpha beta Ii complexes on the cell surface. Furthermore, biochemical analysis and peptide presentation assays demonstrated that transfectants with stable surface alpha beta Ii complexes expressed very few free alpha beta heterodimers at the surface and were very inefficient in their ability to present immunogenic peptides to T cells. These results support the hypothesis that the cytoplasmic domain of Ii is responsible for endosomal targeting of alpha beta Ii and directly demonstrate that association with Ii interferes with the antigen presentation function of class II molecules.